‘LEGIS ACTIO SACRAMENTO IN REM’ AS A RITUAL - Novák, Marek (Zeszyty Prawnicze, 2024)
A ritual can be characterised as a form of conduct based on traditional and established rules. The basic purpose of its use is to confirm the validity of a particular action. Ritual consists of a set of precisely prescribed formal gestures, words or even movements. Undoubtedly, in legal practice the largest use of ritual and formal conduct is in procedural law, which is full of ritual formulas. To some extent, this is true of contemporary legal orders, but it is absolutely self-evident when we look at the earliest extant records of the ancient Roman process of legis actio sacramento in rem, which is described in detail in Gaius’ Institutions. This strictly formal procedure was fully ritualised and based on the parties using prescribed oral formulae. In many cases, the words and gestures could have had a constitutive character, provided they were performed in the prescribed manner. However, this was undoubtedly true of legal actions derived from civil proceedings, for example, in iure cessio, a form of transfer of ownership in which the transferor and transferee merely pretended to conduct legal proceedings in order to achieve a diﬀerent kind of objective, transfer of ownership. An addictio with constitutive eﬀect transferred the property to the transferee and could therefore be considered a performative utterance as defined by J.L. Austin.